Integrating Animations in Chinese Character Writing Based on Cognitive Theory of Multimedia Learning to Promote Students’ Writing Skills - Tin, Tan Geok; Atan, Noor Azean; Mohamad Said, Mohd Nihra Haruzuan; Ali, Mohd Fazli; Mohd, Sanitah; Abd Hamid, Mohd Zolkifli (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The complexity of Chinese character caused students facing learning difficulty in mastering the Chinese character writing skills. This study aimed to investigate the effect and students’ perception on the implementation of animation in teaching and learning of Chinese character writing based on Cognitive Theory of Multimedia Learning (AniCC Online Learning) via Frog VLE platform. Meanwhile, the relationship of implementation of AniCC Online Learning and pupil’s writing performance was also studied to have further insights into the Chinese character teaching and learning situation. Pre-experimental one group pre-test and post-test design were adopted and thirty three Year 1 students were selected as the respondents in this research which involved four types of instruments. There was a significant different (p = 0.013) between the scores of pre-test and post-test for students’ writing performance after performing paired samples t-test. The study also showed an increase in the means scores of students’ writing skills and an increase in the percentage of students’ writing skills ranking at rank 4 or above although no significant different (p = 0.180) was observed between the pre writing assessment and post writing assessment after Wilcoxon Test was performed. The students overall showed high acceptance towards integration of AniCC Online Learning with overall mean score 0.90 (maximum = 1). In sum, the design of AniCC Online Learning via Frog VLE platform is able to improve writing performance as well as to help students in their writing skills.